Feasibility and safety of the 5 Fr Glidesheath Slender in female patients: A randomized controlled trial - Saumya Gupta; Sharad Chandra; Ayush Shukla; Gaurav Chaudhary; Akhil Sharma; Sudhanshu Kumar Dwivedi; Rishi Sethi; Akshyaya Pradhan; Pravesh Vishwakarma; Monika Bhandhari; Abhishek Singh (Heart India)
Background: Numerous previous studies have explored transradial coronary angioplasty, yet none have exclusively focused on the female population. Aim: The aim of this study was to assess the feasibility and safety of the 5 Fr Glidesheath Slender (GSS) (Terumo, Tokyo, Japan) in comparison to the 6 Fr Standard Sheath (SS) in Indian female patients undergoing coronary angiography or percutaneous coronary intervention (PCI). Materials and Methods: This was a prospective, randomized controlled, single-center study. A total of 100 female patients diagnosed with coronary artery disease undergoing invasive coronary angiography and/or PCI through the transradial approach were included. Patients were randomized in 1:1 manner into two groups: 5 Fr GSS and 6 Fr SS groups. Results: Procedural success was achieved in 96.0% and 100.0% of patients in the 5 Fr GSS and 6 Fr SS groups, respectively. Grade I (5 Fr GSS: 0.0% and 6 Fr SS: 8.0%), Grade II (5 Fr GSS: 4.0% and 6 Fr SS: 8.0%), and Grade III (5 Fr GSS: 2.0% and 6 Fr SS: 6.0%) radial hematoma occurred more often in the 6 Fr SS group than the 5 Fr GSS group (P = 0.040). Radial occlusion rates were 0.0% and 6.0% in the 5 Fr GSS and 6 Fr SS groups, respectively. Radial spasm rates were 4.0% and 0.0% in the 5 Fr GSS and 6 Fr SS groups, respectively. Conclusion: Transradial coronary interventions of noncomplex lesions can be successfully performed with either 5 Fr or 6 Fr sheaths, with a tendency of higher procedural success rates in both the 5 Fr GSS and 6 Fr SS groups and lower vascular access complications among 5 Fr GSS in comparison to 6 Fr SS.